Real-Time RIC/RAN Intelligent Controller: A Software Component for Open RAN Architecture - Khan, Imran (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
This research article explores the role and significance of Real-Time RIC (RAN Intelligent Controller) in the context of Open RAN architecture. Open RAN represents a paradigm shift in the telecommunications industry, aiming to disaggregate and virtualize network functions to promote interoperability, flexibility, and innovation. The Real-Time RIC, as a pivotalsoftware component within Open RAN, plays a crucial role in orchestrating and optimizing radio resources in real-time. This article delves into the functionalities, architecture, and implementation considerations of the Real-Time RIC, highlighting its capabilities in enabling dynamic network optimization, intelligent traffic steering, and efficient resource utilization. Furthermore, the article discusses the challenges and opportunities associated with deploying Real-Time RICs in diverse network environments, emphasizing the need for standardization, interoperability, and performance optimization. Through a comprehensive analysis, this research article aims to provide insights into the design, deployment, and impact of Real-Time RICs in advancing the evolution of Open RAN architectures.